Persistence of chronic cough in a community-based population - Lätti, Anne M. (ERJ Open Res, 2020)
Chronic cough causes significant impairment in the quality of life and is often immune to treatment. Previous studies about its persistence have focused on patients managed in special cough clinics. Little is known about the persistence of chronic cough in unselected populations. In this prospective follow-up study, we investigated factors that predict the persistence of cough at 12-month follow-up in a community-based study of subjects with chronic cough. The first e-mail survey in 2017 included a questionnaire about current cough and its risk factors. The 264 subjects who reported chronic cough were sent a follow-up questionnaire 12 months later. The response rate was 77.7% (205 subjects), of whom 165 subjects (80.5%) still had cough in 2018. In multivariate analysis, the following baseline factors predicted the persistence of cough at 12 months; gastro-oesophageal reflux disease (adjusted OR (aOR) 5.02 (95% CI 1.10–22.83)), presence of a chemical trigger (aOR 2.88 (95% CI (1.20–7.00)), duration of cough more than 1 year (aOR 2.80 (95% CI 1.27–6.22)), frequent somatic symptoms (aOR 1.31 (95% CI 1.07–1.59)), and low number of family members (aOR 0.71 (95% CI 0.52–0.98)). In conclusion, most patients with chronic cough still suffer from cough 1 year later. The presence of gastro-oesophageal reflux disease is the main predictor for the persistence of cough.